Learning Transformation in the Digital Era: Teacher Strategies to Enhance Student Engagement - Arifin, Inaya; Mustofa, Triono Ali (FKIP - Universitas Riau, 2025)
This study focuses on the strategies of Islamic religious education teachers in integrating Islamic Religious Education (PAI) learning with digital technology, which is useful for engaging students actively and increasing their engagement during the learning process. The purpose of this study is to describe and analyze PAI teachers' strategies in integrating digital technology. The method used was qualitative, with primary and secondary data sources. The data collection process included interviews, observations, and documentation. The findings show that digital technology integration in PAI learning fosters students’ creative, critical, and active engagement which is reflected in students improved engagement and learning outcomes, with average achievement scores exceeding 80. The implemented learning strategies include selecting appropriate materials to present the material to students in a visual and interactive manner. Furthermore, managing student participation through digital technology increases student engagement. This strategy is useful for positively influencing student interaction and collaboration with digital technology in PAI subjects.